Mimicking dominant negative inhibition of prion replication through structure-based drug design - Perrier, Véronique (The National Academy of Sciences, 2000)
Recent progress determining the structure of the host-encoded prion protein (PrP(C)) and the role of auxiliary molecules in prion replication permits a more rational approach in the development of therapeutic interventions. Our objective is to identify a new class of lead compounds that mimic the dominant negative PrP(C) mutants, which inhibit an abnormal isoform (PrP(Sc)) formation. A computational search was conducted on the Available Chemicals Directory for molecules that mimic both the spatial orientation and basic polymorphism of PrP residues 168, 172, 215, and 219, which confer dominant negative inhibition. The search revealed 1,000 potential candidates that were visually analyzed with respect to the structure of this four-residue epitope on PrP(C). Sixty-three compounds were tested for inhibition of PrP(Sc) formation in scrapie-infected mouse neuroblastoma cells (ScN2a). Two compounds, Cp-60 (2-amino-6-[(2-aminophenyl)thio]-4-(2-furyl)pyridine-3,5-dicarbonitrile) and Cp-62 (N′1-({5-[(4,5-dichloro-1H-imidazol-1-yl)methyl]-2-furyl}carbonyl)-4 methoxybenzene-1-sulfonohydrazide), inhibited PrP(Sc) formation in a dose-dependent manner and demonstrated low levels of toxicity. A substructure search of the Available Chemicals Directory based on Cp-60 identified five related molecules, three of which exhibited activities comparable to Cp-60. Mimicking dominant negative inhibition in the design of drugs that inhibit prion replication may provide a more general approach to developing therapeutics for deleterious protein–protein interactions.